2016
DOI: 10.1017/s1368980016001257
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in the association between food away-from-home consumption and body weight outcomes among Chinese adults

Abstract: Objective: The present study aimed to explore the associations between food away-from-home (FAFH) consumption and body weight outcomes among Chinese adults. Design: FAFH was defined as food prepared at restaurants and the percentage of energy from FAFH was calculated. Measured BMI and waist circumference (WC) were used as body weight outcomes. Quantile regression models for BMI and WC were performed separately by gender. Setting: Information on demographic, socio-economic, diet and health parameters at individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 35 publications
7
18
0
Order By: Relevance
“…The percentage of the population with a high school education or above was 37.8%. There were 74.7% and 71.6% of subjects without smoking and alcohol intake, respectively, similar to what reported elsewhere [ 14 ]. The frequency of the categories of high consumption of fruit and vegetables was 1.2 and 4.3 times/day, respectively.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The percentage of the population with a high school education or above was 37.8%. There were 74.7% and 71.6% of subjects without smoking and alcohol intake, respectively, similar to what reported elsewhere [ 14 ]. The frequency of the categories of high consumption of fruit and vegetables was 1.2 and 4.3 times/day, respectively.…”
Section: Resultssupporting
confidence: 90%
“…Detailed information, including amount consumed, cooking method, and eating location, on three meals and snacks for each individual, was obtained through a face-to-face interview of 24 h dietary recalls and recorded using a tablet device (Lenovo ThinkPad Tablet 2, Lenovo, Beijing, China) by trained staff across three consecutive days, including two weekdays and one weekend day [ 4 , 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…however, opposite to previous research [32] lower rate of frequency of eating out was found among children from high-income family, which may be related to the fact that the rate of overweight and obesity was higher among children from high-income family, then they were less likely to eat out . Furthermore, The study showed that in comparison with children in rural regions, children from urban regions tended to be overweight and obesity, and this difference was also found in other domestic studies [ 42,43], which was likely due to the convenience of eating out in the urban regions [44]. Similar result was founded in a survey conducted among Mexican children found that urban children [45] consumed more energy daily than those in the rural regions.…”
Section: Discussionsupporting
confidence: 82%
“…Li Miao found that children from high income family with more pocket money were more likely to be overweight and obesity [41]. Furthermore, The study showed that in comparison with children in rural regions, children from urban regions tended to be overweight and obesity, and this difference was also found in other domestic studies [ 42,43], which was likely due to the convenience of eating out in the urban regions [44]. Similar result was founded in a survey conducted among Mexican children found that urban children [45] consumed more energy daily than those in the rural regions.…”
Section: Discussionsupporting
confidence: 60%